Chronic subdural hematoma that developed after a diagnostic lumbar puncture: headache worsens with bilateral compression of jugular veins (Queckenstedt’s maneuver) - Valença, Marcelo Moraes; Bem Junior, Luiz Severo; Silva, Ana Cristina Veiga da; Silva, Ubiratan Alves Viturino da; Valença, Marcelo Andrade; Silva, Alberto Henrique Torres Trindade da; Carvalho, Déborah Emmily de; Fortes, Henry Martins Soares; Valença, Martina Falcão; Andrade-Valença, Luciana Patrízia Alves de (Headache Medicine, 2022)
Image in Headache Medicine